Comparação de métodos para avaliação postural em operação de máquinas agrícolas - Possebom, Gessieli (2018)
Agriculture is a very old activity and its development in the country in recent decades is strongly linked to the great technological evolution of agricultural machinery and equipment. On the other hand, the increasing use of machinery contributed to the increase of some risks of accidents and especially injuries or postural disturbances in rural areas. Thus, early identification of inappropriate postures, through postural analysis methods, however, has become an important tool for operator safety and comfort. The objective of this work is to perform a comparative analysis between the ergonomic evaluation methods RULA, REBA, OWAS and TOR-TOM, seeking to highlight the versions and differences for their use, during the operation of agricultural machines. The study was carried out through an exploratory research in Boa Vista of INCRA, RS, in the month of August, 2017, during a soil preparation operation, with the sub-tractor set. Initially a questionnaire was applied, seeking to collect information from the operator, as well as the machine and implement used. For analytical analysis, a soil preparation operation was filmed for a period of 10 hours. Afterwards, one hour of representative video judged, sectioned in photos and selected 100 sequential images were selected. These images were analyzed by the RULA, REBA, OWAS and TOR-TOM methods through the software Ergolândia 5.0 with the aid of complementary noise, temperature and force information. As comparative analyzes, an ease of application, an importance of the posture and complementary variables, and a range of activity and postural factors were analyzed. The OWAS method presented the highlight for the facilitation of the application, while the REBA methods, followed by the RULA, stood out for the importance of the posture variables. For the importance of the complementary variables, the RULA, followed by the REBA, deserve to be highlighted as the most indicated. Similar results were obtained for the inclusion of the posture factors, with emphasis on the two methods. Regarding the range of activity factors, TOR-TOM obtained the most satisfactory results. Analysis of agricultural machine operators, in 94% of the total time of the operation, a posture can be considered acceptable for the maintained for long periods. Thus, a comparative analysis showed the RULA method as the most suitable for postural analysis in agricultural machines, besides the REBA method, because it presents very similar situations, contemplating whole body analyzes. The TOR-TOM method presents the most favorable conditions of analysis.